Framing Climate Change News In Indonesian Online Media: Nvivo Based Qualitative Analysis - Prasetyanto, Wicitra Dewanggana (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the framing of news about climate change in Indonesian online media by identifying the types of framing, the actors, the news tone, and the temporal dimension used. This research uses a qualitative approach, supported by NVivo software. The data are news articles from several national online media th, selected purposively and then coded using a deductive-inductive coding approach. The study's findings are news related to climate change, framed within the disaster-within-a-disaster framework. Most economic narratives in the news feature government officials and experts, while the public is portrayed as the affected party. The tone of the news is generally optimistic and solution-oriented, and it emphasizes its impacts. These findings more clearly indicate that the media not only represent climate change as an environmental crisis but also as a development and strategic policy issue. This research is expected to enrich the study of enriched media in Indonesia. In addition, it can encourage Indonesian media research to strengthen the media's role as a source of information for adaptive policy responses to climate change.